Total Quality Management in Theorie und Praxis Zum ganzheitlichen Unternehmensverständnis - Rothlauf, Jürgen (De Gruyter Oldenbourg, 2014)
In order to survive the pressures of international competition, one needs a comprehensive perspective on all entrepreneurial activities. The integrated structure of Total Quality Management (TQM) fulfills this expectation, because it pays attention to all participants along the value creation chain. This book presents TQM in all of its facets and varieties. Prof. Dr. Jürgen Rothlauf (Fachhochschule Stralsund)